Costs, revenues and profits: an economic analysis of smallholder tobacco farmer livelihoods in Malawi. Issue 6 (8th October 2016) - Makoka, Donald; Drope, Jeffrey; Appau, Adriana; Labonte, Ronald; Li, Qing; Goma, Fastone; Zulu, Richard; Magati, Peter; Lencucha, Raphael
Abstract : Background: The preservation of the economic livelihood of tobacco farmers is a common argument used to oppose tobacco control measures. However, little empirical evidence exists about these livelihoods. We seek to evaluate the economic livelihoods of individual tobacco farmers in Malawi, including how much money they earn from selling tobacco, and the costs they incur to produce the crop, including labour inputs. We also evaluate farmers' decisions to contract directly with firms that buy their crops. Methods: We designed and implemented an economic survey of 685 tobacco farmers, including both independent and contract farmers, across the 6 main tobacco-growing districts. We augmented the survey with focus group discussions with subsets of respondents from each region to refine our inquiries. Results: Contract farmers cultivating tobacco in Malawi as their main economic livelihoods are typically operating at margins that place their households well below national poverty thresholds, while independent farmers are typically operating at a loss. Even when labour is excluded from the calculation of income less costs, farmers' gross margins place most households in the bottom income decile of the overall population. Tobacco farmers appear to contract principally as a means to obtain credit, which is consistently reported to be difficult to obtain. Conclusions: The tobacco industry narrative that tobacco farming is a lucrative economic endeavour for smallholder farmers is demonstrably inaccurate in the context of Malawi. From the perspective of these farmers, tobacco farming is an economically challenging livelihood for most.